Reptilia, Squamata, Dipsadidae, Tomodon orestes Harvey and Muñoz, 2004: Distribution extension, new country record - Akmentins, Mauricio Sebastián (2010)
We report the first record of Tomodon orestes Harvey and Muñoz, 2004 for Argentina. An adult male was collected in November 2008 in an open grassland habitat in the locality of Vallecito, Santa Victoria department, Salta province, Argentina. This new record is the southernmost locality for the species extending its distribution range ca. 95 km straight-line south from type locality.